Pengaruh Kemampuan Manajerial Kepala Madrasah dan Iklim Psikologis Terhadap Kinerja Guru Madrasah Tsanawiyah Negeri Lahat - Moh Ali Akbar (Studia Manageria, 2019)
This study aims to determine the effect of the managerial ability of madrasa principals, and psychological climate on the performance of MTs Negeri Lahat teachers both partially and together. The study that is used is survey methods. Research respondents were 49 teachers as samples. Questionnaire instruments regarding the performance of madrasah teachers as the dependent variable, managerial ability of the madrasah head,and psychological climate as independent variables and analysis tools using multiple linear regression methods. The study used a questionnaire instrument to measure each variable: (1). Madrasa head managerial ability variable, (2). Psychological climate variables, (3). Teacher performance, which was developed into 12 questionnaire items each. From the results of the study found that: (1). Madrasa head managerial ability variables partially have a significant effect on the performance of madrasah teachers, these results can be seen and the value of the T test which indicates a significance value of less than 0.05. (2). The psychological climate variable partially has no effect on the performance of teachers in MTs NegeriLahat with (P-value = 0.281> 0.05). In the F test obtained a significant level of 5% then with a significant level of 0,000 (P-value <0.05) then H0 is rejected and Hi is accepted. This means that it can be concluded that there is a linear relationship between the managerial ability of the madrasa head (Xi) and the psychological climate (X2) together to the teacher's performance (Y).